Women in the Ottonian Church: an Iconographic Perspective - McKitterick, Rosamond (Studies in church history, 1990)
Although the principal relationship observable in an early medieval manuscript illustration is that between the artist and his or her text, the interests of the reader, and in many cases the first owner or commissioner of an illustrated book, could to some degree determine the extent and the elaboration of the illustrations, and, possibly, aspects of the iconography. The incidence of women in the illustrations of Christian books of the Carolingian and Ottonian periods, therefore, is a potentially fruitful source for examining the attitudes towards women’s role in the Church in the early Middle Ages. It may be possible to see, firstly, whether the prominence of women in the New Testament, and in the Gospels in particular, is enhanced and elaborated in ninth- and tenth-century visual interpretations of these Christian texts, or, secondly, whether there are any other innovations in Carolingian or Ottonian illustrations which shed light on the religious work of women within the Church. But to what extent is this potential realized? Are omissions as significant as inclusions? Can we conclude much from the relative dearth of pictures of women in Carolingian books, as opposed to the greater number of women portrayed in Ottonian books? It is the purpose of this paper to examine this phenomenon and its context and thereby to suggest some preliminary explanations.